Alternative Approaches To Hydro Compensation And Agreements With First Nations: Manitoba and Quebec - Loxley, John (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2012)
This paper outlines the workings of two quite different contemporary approaches to settlements and agreements with First Nations by hydro companies and governments involved in hydro dam construction. The first is the equity approach used by Manitoba Hydro in negotiations with the Nisichawayasikh Cree Nation (NCN) in which the First nation is effectively offered joint ownership of the dam and a share in future income streams and in employment and construction benefits. The second approach is that by the James Bay Cree of northern Quebec who eschew dam ownership, instead negotiating an annual share in revenues generated by hydro, forestry and mining. Both approaches constitute major improvements over disastrous earlier approaches which can be summarized as 'flood now and talk later', but they carry quite different economic. Political and governmental terms as well as quite different potential benefits and risks. This paper examines the background behind each deal and the way in which they operate. It concludes by arguing that each deal was conditioned by circumstances and history. There is, however, clear merit in Aboriginal People seeking to secure maximum control over and benefit from all sources of economic development on their traditional lands.